A Comprehensive Look at the Development of Asthma in Children - Ileana Diana Diaconu; Veronica Gheorman; Gabriela Adriana Grigorie; Cristian Gheonea; Tiberiu-Stefanita; Beatrice Mahler; Ion Alexandru Voropanov; Mihnea Cristian Firoiu; Andreea Silvia Pîrvu; Alexandru Bogdan Popescu; Renata Văruț (MDPI AG, 2024)
Asthma, a prevalent chronic respiratory condition affecting millions of children globally, presents a significant health challenge. This review critically examines the developmental pathways of asthma in children, focusing on genetic, environmental, and early-life determinants. Specifically, we explore the impact of prenatal and postnatal factors such as maternal smoking, nutrition, respiratory infections, and allergen exposure on asthma development. Our analysis highlights the intricate interplay of these influences and their contribution to childhood asthma. Moreover, we emphasize targeted strategies and interventions to mitigate its burden, including genetic counseling for at-risk families, environmental modifications to reduce triggers, and early-life immunomodulation. By delving into these preventive measures and interventions, our review aims to provide actionable insights for healthcare professionals in developing tailored strategies to address the complexities of childhood asthma. In summary, this article offers a detailed examination of asthma development in children, aiming to enhance understanding and inform efforts to reduce its burden through targeted interventions.